Astigmatismo Miopico hereditario en paciente femenino de 25 años de edad. - Santamaria Benavides, Kerly Isabel (2021)
The present clinical case is about a 25-year-old female patient who has been diagnosed with (AM) hereditary Myopic Astigmatism, this is characterized by being a combination of both refractive errors causing blurred and distorted vision causing the vision of far from being affected, so it is unlikely to ignore it. The objective of this research is to evaluate hereditary MA in a 25-year-old female patient. The methodology is based on the analysis of the clinical history, personal and family pathological antecedents, physical examinations such as AVL, AVSC, AVCC that served to make a definitive diagnosis and prescribe treatment. Some of the symptoms that the patient presented were: headache, sleepiness, lack of concentration, difficulty seeing from afar and blurred vision; the established treatment is based on negative sphero-cylindrical monofocal moons. In conclusion, it was recommended that you undergo a minimum exam once a year, eat a good diet, properly clean your optical devices and reduce the use of electronic devices that emanate LED light and are harmful to the eyes.